Calidad del servicio del Hospedaje Entre Dos de la ciudad de Iquitos, abril 2022 - Sifuentes Tote, Tony Jhony (2023)
The thesis Quality of the Lodging Service between two in the city of Iquitos, April 2022, has as its general objective to analyze the dimensions of the quality of service in the lodging between two in the city of Iquitos, period April 2022, the research is of level descriptive, basic type of non-experimental and cross-sectional design. The population consisted of 35 external clients, which is the monthly average number of room users. The results show that 85.7% of the external clients have a good perception of the quality of the service; Regarding the dimensions, security and empathy stand out with perceptions of 85.7% as good, with the intangible aspects dimension being the one that has a good rating with only 14.30%, its highest rating being regular with 80.0%.